A natural infection by the red sea bream iridovirus‐type Megalocytivirus in the golden mandarin fish Siniperca scherzeri. Issue 8 (28th May 2018) - Kim, K I; Hwang, S D; Cho, M Y; Jung, S H; Kim, Y C; Jeong, H D
Abstract: An outbreak of a Megalocytivirus infection was found in the golden mandarin fish Siniperca scherzeri during September and October 2016, in Korea. Phylogeny and genetic diversity based on the major capsid protein (MCP) and adenosine triphosphatase (ATPase) genes showed a new strain. Designated as GMIV, this strain derived from the golden mandarin fish was suggested to belong to the red sea bream iridovirus (RSIV)‐subgroup I. Additionally, this train clustered with the ehime‐1 strain from red sea bream Pagrus major in Japan and was distinguished from circulating isolates (RSIV‐type subgroup II and turbot reddish body iridovirus [TRBIV] type) in Korea. The infection level, evaluated by qPCR, ranged from 8.18 × 10 2 to 7.95 × 10 6 copies/mg of tissue individually, suggesting that the infected fish were in the disease‐transmitting stage. The diseased fish showed degenerative changes associated with cytomegaly in the spleen as general sign of Megalocytivirus infection. The results confirm that the RSIV‐type Megalocytivirus might have crossed the environmental and species barriers to cause widespread infection in freshwater fish.